On track to tackle dengue: History and future of NS4B ligands - Behnam, Mira A. M.; Klein, Christian D. (Cell host and microbe, 2021)
A recent publication in Nature (Kaptein et al., 2021) reports a highly potent antiviral compound against dengue with promising efficacy in mice. Here, we track the history of this compound class, its pharmacology, and its chemistry, with insights into its potential as orally available drugs to prevent and treat dengue.
Gesehen am 15.02.2022